Isolation matters—processing blood for Raman microspectroscopic identification of bacteria - Lorenz, Bjoern; Roesch, Petra; Popp, Jürgen (Analytical and Bioanalytical Chemistry, 2019)
Bacteremia with its high mortality is a frequent case in clinical health care. Further, bacteremia includes the considerable risk of progressing to a sepsis. Even in case of survival, sepsis still entails diminished quality of life for the survivors and high indirect cost for the society. The crucial factor in sepsis is time. Therefore, timely description of adequate antibiotics is vital to reduce mortality and improve quality of life after survival. Despite that, the current gold standard of clinical bacteria diagnostic is based on cultivation of bacteria, which requires an average of 13-h cultivation. Consequently, there is a necessity for culture free identification methods without sacrificing the range of bacteria strains which can be identified. Raman microspectroscopy in general requires only single bacteria cells and has proven to offer high identification accuracies. However, the prerequisite for Raman microspectroscopy is a suitable isolation strategy to obtain single unharmed bacteria cells free from matrix. Moreover, in blood, bacteria are outnumbered by billions of blood cells. In this study, we present an isolation strategy to recover single bacteria cells from blood and evaluate their suitability for Raman microspectroscopic identification. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-04-20
Keywords: Bacteria; Blood; Identification; Isolation; Lysis; Raman microspectroscopy